MACROSCOPIC EVALUATION OF INCISION WOUND HEALING IN THE SKIN OF WHITE RATS TREATED WITH PLATELET-RICH PLASMA GEL DERIVED FROM PIG BLOOD - Sukma, Made Amara Sanjiwaning; Wirata, I Wayan; Gunawan, I Wayan Nico Fajar; Sudisma, I Gusti Ngurah; Kardena, I Made (Buletin Veteriner Udayana, 2025)
Wound healing is the body's attempt to restore its structural integrity and normal function after tissue disruption. Platelet Rich Plasma (PRP) is often used as a regenerative treatment by increasing the activity of growth factors in the blood to treat damaged tissue. Pig blood contains a high concentration of platelets that can support the wound healing process. The purpose of this study was to determine the macroscopic picture of incision wound healing on the skin of white rats given PRP gel from pig blood. The experimental animals used in this study were 27 wistar strain rats. There were three treatments carried out, namely the negative treatment group given 0.9% NaCl solution, the positive control group given bioplacenton, and the treatment group with pig blood PRP gel. Parameters used to determine the level of wound healing include wound length, wound color, wound moisture, and wound scab. Wound length data was analyzed using one-way analysis of variance (Anova). Meanwhile, data on wound color, wound scab, and wound moisture were analyzed by Kruskal Walls. The pig blood PRP gel treatment group had a significant effect on the incision wound healing rate than the negative and positive treatment groups (bioplacenton). PRP gel from pig blood can accelerate wound healing because it contains many growth factors that play an important role in tissue repair and regeneration. Further research is recommended to evaluate the effect of PRP on other types of wounds, such as burns or infectious wounds, as well as developing PRP preservation methods in other forms for wider clinical applications.